The possibility of early diagnosis of colorectal cancer through expression of Lncrna UCA1, Lncrna LINC00970, and Wnt genes; an in-vitro study - Seyedeh Medisa Sadat Razavi; Narges Maleki; Faranak Jamshidian (Acta Scientiarum. Health Sciences, 2022)
Colorectal cancer is the 4th cause of cancer death; with considering the growth process of this cancer and the necessity of early diagnosis, the purpose of the research is to state the LncRNA 00970, LncRNA UCAI, and the Wnt gene before and after the treatment by 5-Azacytidine epigenetic medicine, to reach the biomarker in the very first steps of colorectal cancer. In this experiment, the human colon cancer cell line (HT29) treated with different concentrations of 5-aza-2’-deoxycytidine (5-aza-dC) was utilized to induce DNA demethylation; Quantitative PCR (qPCR) was used to measure LncRNA UCA1 and LncRNA LINC00970 and Wnt expression. There was a significant relationship between the expression of LncRNA 00970, LncRNA UCAI, and the Wnt gene and its effects on colorectal (p < 0.05). The Wnt gene was treated by 1 and 10 of 5-Azacytidine epigenetic medicine, which then experienced decreases. In LncRNA UCAI and LncRNA00970 in dose 1 micromolar of 5-Azacytidine had decrement and increment of expression respectively that explains their efficiency but in treatment by dose 10 mM of this medicine, no significant LncRNA expression difference was detected, 5-azacitidine has a direct impact on its target genes and LncRNAs. Therefore, it can be used in the early diagnosis of colorectal cancer.